Enhancing of asphaltene adsorption onto Fe3O4 nanoparticles coated with metal-organic framework Mil-101 (Cr) for the inhibition of asphaltene precipitation. Issue 3 (4th March 2018) - Setoodeh, Narjes; Darvishi, Parviz; Lashanizadegan, Asghar
ABSTRACT: In this study, the potential of MOF (Mil-101-Cr)-coated Fe3 O4 magnetic nanoparticles (Fe3 O4 -MOF MNPs) for asphaltene adsorption was investigated for the first time and the results were compared with magnetic Fe3 O4 nanoparticles (Fe3 O4 MNPs). The coprecipitation method was used for the synthesis of both nanoparticles and were verified using x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FE-SEM). The initial asphaltene concentration, nanoparticles concentration, and temperature were the investigated parameters that influenced the adsorption capacity. Increasing the asphaltene concentration, decreasing the mass of nanoparticles, and reducing the temperature could enhance the maximum asphaltene adsorption capacities of 0.79 for Fe3 O4 MNPs and 0.98 mg m −2 for Fe3 O4 -MOF MNPs. Adsorption isotherms tests showed that the Langmuir model was in agreement with the experimental data. In addition, the evaluation of adsorption kinetics demonstrated that the pseudo-second-order Lagergren model predicted the results more precisely. The amount of asphaltene adsorption for Fe3 O4 -MOF MNPs was higher than that for Fe3 O4 MNPs. These results recommend the application of MOF as an appropriate and effective coating for enhancing asphaltene adsorption. GRAPHICAL ABSTRACT: